2006
DOI: 10.1177/070674370605101107
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Characteristics of Participants in Studies of Risk Factors, Prevention, and Treatment of Postpartum Depression

Abstract: Objectives: Metaanalyses have found that sociodemographic variables are not strong predictors of postpartum depression. However, no studies have systematically examined the extent to which the samples used in published research on postpartum depression have included sufficiently diverse samples of women to merit this conclusion. The objectives of this study were to examine the demographic characteristics of participants in previously published studies and to document existing gaps in the current literature. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 42 publications
1
25
1
1
Order By: Relevance
“…Public health and clinical concerns about prenatal psychiatric disturbance are most acute for minority women of lower socioeconomic status who exhibit increased prevalence of depressive symptoms (36). For example, a large-scale study of low income minority pregnant women reported that 29.3% (7) had experienced a traumatic event; another study of a similar population reported rates of post traumatic stress disorder (PTSD) to be 7.7% (8).…”
Section: Introductionmentioning
confidence: 99%
“…Public health and clinical concerns about prenatal psychiatric disturbance are most acute for minority women of lower socioeconomic status who exhibit increased prevalence of depressive symptoms (36). For example, a large-scale study of low income minority pregnant women reported that 29.3% (7) had experienced a traumatic event; another study of a similar population reported rates of post traumatic stress disorder (PTSD) to be 7.7% (8).…”
Section: Introductionmentioning
confidence: 99%
“…While in some studies, supplemental insurance and patient-centered healthcare system facilitated the conditions for a successful pregnancy, as the evidence for this claim is the conclusion of Ross et al 's study. [26]…”
Section: Discussionmentioning
confidence: 99%
“…18 In a meta-analytic review, O'Hara and Swain 19 identified the following consistent risk factors for postpartum depression: lower socioeconomic status, life stress during pregnancy, a difficult pregnancy, marital discord, lack of social support, prior psychopathological condition, and a vulnerable personality. These same factors and self-esteem, childcare stress, prenatal anxiety, infant temperament, and unplanned/unwanted pregnancy were identified by Beck 20 in her updated meta-analysis.…”
Section: Psychosocial Risk Factors For Maternal Depressionmentioning
confidence: 99%